Problematic internet and Facebook use and online gaming among university student: an exploratory study - Dias, Paulo (2021)
Advances in technology have introduced new challenges and issues for policymakers and researchers. There is some debate in the literature whether the Internet, Facebook, and online gaming addictions may be true addiction disorders or are all manifestations of a more general information technology addiction. The purpose of this study is to explore gender differences in problematic Internet and Facebook use and online gaming, and the independence of these phenomena. The study sample comprised 500 college students, who completed a sociodemographic questionnaire, the Internet Addiction Test, Bergen Facebook Addiction Scale, and Online Gaming Scale. Males had more problems related to online gaming, and more problematic Internet and Facebook use. A bifactor model with one general and three specific factors - problematic online gaming, problematic Internet use and problematic Facebook use - obtained the best fit to the data. However, the specific variance explained by the factors of problematic Internet and Facebook use was low, but high in the case of problematic online gaming. Therefore, problematic online gaming seems to have more distinctive characteristics than the other two types of behavioural addictions.